2014
DOI: 10.1002/pssc.201300575
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CdMnTe crystal grown with vertical Bridgman method under Te‐rich conditions

Abstract: In this study, the Indium (In) doped Cd1–xMnx Te (xMn=0.1, CdMnTe) crystals with excess Te in the amount of 0 and 1.2 at% were grown by the Bridgman method. The segregation coefficient of In dopants distributions in the CdMnTe crystals with and without excess Te were determined to be 0.08 and 0.11, respectively. The IR transmission microscopy shown that the size of Te inclusions in CdMnTe crystal with excess Te increased to 5–13 μm with the concentrations of (2–3)×105 cm–3. The PL spectra indicated the formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…For the CMT crystals grown by Bridgman methods, it was commonly observed that a high density of Te inclusions were formed in the as-grown crystals, especially along grain or twin boundaries. [5,9] These inclusions can distort the local internal electric field in CMT detectors and entail significant fluctuations in the total charge-collection by trapping free charge-carriers, and therefore, seriously deteriorate the performance of radiation detectors. [13] Results of recent quenching experiments clearly showed that the concave growth interface of CMT results in the trapping of Te-rich liquid droplets as a consequence of morphological instability and therefore, a high density of Te inclusions is formed during the subsequent cool-down period.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the CMT crystals grown by Bridgman methods, it was commonly observed that a high density of Te inclusions were formed in the as-grown crystals, especially along grain or twin boundaries. [5,9] These inclusions can distort the local internal electric field in CMT detectors and entail significant fluctuations in the total charge-collection by trapping free charge-carriers, and therefore, seriously deteriorate the performance of radiation detectors. [13] Results of recent quenching experiments clearly showed that the concave growth interface of CMT results in the trapping of Te-rich liquid droplets as a consequence of morphological instability and therefore, a high density of Te inclusions is formed during the subsequent cool-down period.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] Recently, CMT has attracted increasing interest since it is considered a promising material for the fabrication of high-performance room-temperature x-ray and gammaray detectors. [2][3][4][5] Such detectors offer great potential for nonproliferation applications, medical imaging, astrophysics research, and monitoring industrial processes, because they are able to operate at ambient temperatures, while providing a high detection efficiency and good energy resolution. [6,7] Compared with cadmium zinc telluride (CdZnTe or CZT), a current leading material in such applications, CMT offers several distinct advantages that make it a good candidate in this field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenomenon can be explained by the removal of the impurities [17,22]. Moreover, the DAP peak is relative to the complexes formed by indium and Cd vacancy [24]. Cd atoms diffuse into CMT:In crystals and compensate Cd vacancies in the complexes.…”
Section: Effect Of Multi-step Annealing On Pl Spectramentioning
confidence: 99%
“…Thus, the best signal-to-noise ratio of CMT radiation detector can be achieved by relatively low manganese content. [10] Although CMT has many advantages, researchers have encountered many obstacles in studying it. As is known to all, the performance of CMT detector with no defects is better than that of flawed one.…”
Section: Introductionmentioning
confidence: 99%